Komunikasi Pemasaran Objek Wisata Aan Secret Waterfall Berbasis Digital - A.A.Ngr. Oka Suryadinatha Gorda; Ketut Bayu Surya Prayoga; Ni Putu Yunita Anggreswari (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Aan Secret Waterfall tourism object has interesting potential to be visited by tourist. This tourist attraction presents the beauty of a waterfall and also offers a very beautifull cliff view coupled with the condition of Aan Village which is still beautifull and views of rice fields, as well as hills and the sea visible from a distance. However, this tourist attraction still needs to be reorganized and revamped. The level of tourist visits is still not optimal. This is due to a lack of marketing communication. The purpose of this study was to see digital based marketing communications for the Aan Secret Waterfall tourist attraction. The method used in this research is a qualitative approach, data collection using interview techniques, observation, and documentation, checking the validity of the data using triangulation of the sources and techniques. The results of this study indicate that the management uses digital media, namely social media such as facebook, Instagram, and youtube in conducting marketing communications, but managing this digital media is still not optimal. Creating attractive content and consistency is needed in marketing communications through digital media to attract tourist.